2020
DOI: 10.1007/s00464-020-07735-w
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative use of fluorescence with indocyanine green reduces anastomotic leak rates in rectal cancer surgery: an individual participant data analysis

Abstract: Intraoperative use of fluorescence with indocyanine green reduces anastomotic leak rates in rectal cancer surgery: an individual participant data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 26 publications
3
48
0
2
Order By: Relevance
“…To this end, we are now using near-infrared laparoscopy, recently introduced to provide fast and reproducible real-time intraoperative assessment of intestinal microvascularization using indocyanine green angiography [23]. Recent data have suggested that the assessment of perianastomotic microvascularization may be associated with a reduction in the risk of fistula, pleading for the multifactorial etiology of this severe complication [24].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we are now using near-infrared laparoscopy, recently introduced to provide fast and reproducible real-time intraoperative assessment of intestinal microvascularization using indocyanine green angiography [23]. Recent data have suggested that the assessment of perianastomotic microvascularization may be associated with a reduction in the risk of fistula, pleading for the multifactorial etiology of this severe complication [24].…”
Section: Discussionmentioning
confidence: 99%
“…Still, some had various biases or showed insufficient statistical power. However, the overall perception is that ICG does improve the rates of anastomotic complications, especially in left colorectal surgery, with solid randomized controlled trials being expected to confirm this [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICG NIR fluorescence proved to be a reliable tool in evaluation the lymphatic flow and in identifying the SL. However, with a universally accepted lower clinical significance for the concept of SL in colorectal surgery in comparison to breast and skin malignancies, the use of this method in establishing suitable candidates for limited colonic resections remains controversial [ 60 , 62 , 63 , 64 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has reportedly been used for evaluation of residual gastric blood flow in pancreatic resection after gastrectomy [14][15][16]. It has also been reported that ICG fluorescence was used to assess blood flow at the colonic anastomosis to reduce the suture failure rate [17,18]. In esophagectomy, ICG fluorescence has been used to assess gastric conduit blood flow [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%